Contextual Influences on Superintendents’ Time Usage - Jones, Kim; Howley, Aimee (Education Policy Analysis Archives, 2009)
Using data from a survey of superintendents in four states, this study explored how contextual factors and the real and perceived stringency of accountability measures influence the attention superintendents pay to the different roles comprising their work. A major concern was the extent to which stringent accountability was associated with superintendents’ tendency to emphasize educational leadership rather than managerial functions. Recognizing that other circumstances also might contribute to superintendents’ decisions about how to balance their work, the study included five contextual variables: enrollment, locale, SES, funding, and percentage minority. From a sample of 941 superintendents, 68% returned questionnaires. Findings: although superintendents’ perceptions of the stringency of state accountability measures were related to their location in high- or low-stringency states, contextual factors and especially enrollment and the location of a district in a rural region had the most pronounced effects on their attention to managerial tasks. Allocation of time varied by state; however, across states very few superintendents’ devoted the majority of their time to educational leadership.